Investigating web 2.0 tools use and students cognitive engagement in selected Tanzanian higher institutions: preparing towards 21st learning - Malecela, Issa Omar; Syed Hassan, Sharifah Sariah (Al Publications, 2019)
With the availability and affordability of computers and communication technology devices worldwide, teaching no longer centers around teachers. Students become autonomous learners, taking the ownership of learning where they no longer rely fully on teachers as the learning resources. This paves innovative intervention towards engaging the learners cognitively using Web 2.0 tools. Web 2.0 tools offer learners to engage in higher order thinking skills involving not just to understand and apply but also to analyze, evaluate and create through two-way communications and collaborations. Due to the pedagogical potentials of Web 2.0 tools, this study attempts to investigate how the students involve Web 2.0 tools in supporting classroom learning. This study employed a questionnaire survey among students at a Higher Learning Institution involving 100 samples. This is a preliminary study prior to the final study involving bigger populations from different universities. Interviews were also carried out among three students to gain in-depth understanding of learning that enables the researcher to derive a conceptual model. The related main ideas from each interviewee were gathered to get commonality of themes. And finally, main themes were generated. A systematic data analysis was done based on developing themes in an inductive way as directed by the content of data. The findings reveal that the majority of students use Web 2.0 tools for finding resources, communication and for both low and higher order thinking skills. Further findings show that Academic readiness contributed significantly on students cognitive engagement while Use of Web 2.0 tools did not contribute significantly. Implications of the study address the theoretical and practical aspects.